2016
DOI: 10.1111/asj.12589
|View full text |Cite
|
Sign up to set email alerts
|

Validation of feasibility and quality of chicken breast meat cooked under various water‐cooking conditions

Abstract: Under laboratory conditions, the qualities of boneless chicken breasts are commonly determined by placing them in a bag and cooking them in a water bath. The results are often applied as references for comparing the influences of cooking techniques. However, whether a sample cooked under this "laboratory" condition actually represents the meat cooked under the "real-life" condition in which meat is frequently cooked directly in water without packaging remains unclear. Whether the two cooking conditions lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…According to Zhuang and Savage (2008), the broiler chicken meat with water cooking provided higher meat juiciness and lower residue loose particles than the ones cooked with a commercial oven. Similarly, Chumngoen et al (2016b) reported strong correlations between the characteristics of texture profile analysis and corresponding sensory attributes, including hardness, cohesiveness and chewiness. The tenderness of WC meat coincided with its lower shear force (P < 0.001), as shown in Table 1, and agreed with Chumngoen and Tan (2015) who observed a high correlation between descriptive sensory hardness and shear force value of chicken meat.…”
Section: Descriptive Sensory Evaluationmentioning
confidence: 88%
See 4 more Smart Citations
“…According to Zhuang and Savage (2008), the broiler chicken meat with water cooking provided higher meat juiciness and lower residue loose particles than the ones cooked with a commercial oven. Similarly, Chumngoen et al (2016b) reported strong correlations between the characteristics of texture profile analysis and corresponding sensory attributes, including hardness, cohesiveness and chewiness. The tenderness of WC meat coincided with its lower shear force (P < 0.001), as shown in Table 1, and agreed with Chumngoen and Tan (2015) who observed a high correlation between descriptive sensory hardness and shear force value of chicken meat.…”
Section: Descriptive Sensory Evaluationmentioning
confidence: 88%
“…Similarly, Chumngoen et al (2016b) reported strong correlations between the characteristics of texture profile analysis and corresponding sensory attributes, including hardness, cohesiveness and chewiness. Higher MFI value during cooking coincided with elevation of actomyosin dissociation and protein solubility, and reduced shear force values, which eventually contribute to meat tenderness Chumngoen et al 2016b). In the current study, WC meat which had significantly lower sensorial initial hardness and chewdown hardness (Table 3) coincided with its lower shear force value (Table 1) and higher MFI value (Table 2) when compared with OC meat.…”
Section: Descriptive Sensory Evaluationmentioning
confidence: 88%
See 3 more Smart Citations